Bar Layout and Weight Optimization of Special RC Shear Wall. (June 2018) - Hoseini Vaez, Seyed Rohollah; Shahmoradi Qomi, Hamidreza
Abstract: Optimization problems can be defined and formulated with either discrete or continuous variables. This paper presents a continuous optimization method for the design of reinforced concrete shear walls, based on the concept of boundary element and with the reinforcement layout taken into consideration. Contrary to the discrete method, where algorithm must be provided with a set of previously prepared default designs, the continuous optimization algorithm generates and evaluates a wall design in each iteration. The objective function of the algorithm minimizes the cost of the wall, which depends on the reinforcement details (rebar diameter and layout) and the wall dimensions (the cost of concrete and formworking). This objective function consists of the boundary element dimensions and the reinforcement layout variables (cross-sectional area and spacing of rebars). Shear wall design requirements and restrictions are formulated as constraints in accordance with ACI318-11 provisions for special ductility. After obtaining optimal wall design for seismic loads, design details such as wall dimensions and reinforcement details are determined accordingly. The optimization is performed by the use of several metaheuristic algorithms, including PSO, FA, WOA, and CSA. The comparison of the results of continuous and discrete optimization methods show that the shear wall designs obtained by the continuous approach are less expensive and closer to the global optimum.